ANALISIS PEMAHAMAN MAHASISWA PADA MATERI LUAS DAERAH BERDASARKAN KERANGKA WIGGINS DAN TIGHE - Suryanti Suryanti; Cicik Pramesti; Riki Suliana Ranggawati Sidik; Ayu Silvi Lisvian Sari (Universitas Tribhuwana Tunggadewi, 2026)
This study aims to describe the understanding of prospective teacher students on the material of area based on six aspects of Wiggins and Tighe. This descriptive-qualitative study with a case study type involved three students of the Mathematics Education Study Program as subjects. Data were collected through a test of students' understanding of integral applications consisting of three integral application questions about area and in-depth interviews. Data were analyzed qualitatively with data reduction, data presentation and drawing conclusions on the six aspects of Wiggins and Tighe. The results showed that all subjects met the explanation indicator, while the application aspect developed in two subject. On the other hand, weaknesses in the interpretation aspect impacted students’ low ability to develop alternative solution strategies (perspective) and reflect on their thinking processes (self-knowledge). Although all subjects were able to identify the difficulties experienced (empathy), the ability to reflect still emerged after receiving exploratory questions during the interview. The research findings reveal that the interpretation aspect influences the development of the application, perspective, and self-knowledge aspects, so that students’ inderstanding of area cannot be assessed only based on careful solution procedures, buat also through the relationship between aspects of understanding in the Wiggins and Tighe framework